Step-by-step guide to building an inexpensive 3D printed motorized positioning stage for automated high-content screening microscopy. - Gilbert, Daniel; Friedrich, Oliver; Schneidereit, Dominik; Meier, Jochen C; Kraus, Larissa (Biosensors and Bioelectronics, 2017)
High-content screening microscopy relies on automation infrastructure that is typically proprietary, non-customizable, costly and requires a high level of skill to use and maintain. The increasing availability of rapid prototyping technology makes it possible to quickly engineer alternatives to conventional automation infrastructure that are low-cost and user-friendly. Here, we describe a 3D printed inexpensive open source and scalable motorized positioning stage for automated high-content screening microscopy and provide detailed step-by-step instructions to re-building the device, including a comprehensive parts list, 3D design files in STEP (Standard for the Exchange of Product model data) and STL (Standard Tessellation Language) format, electronic circuits and wiring diagrams as well as software code. System assembly including 3D printing requires approx. 30h. The fully assembled device is light-weight (1.1kg), small (33×20×8cm) and extremely low-cost (approx. EUR 250). We describe positioning characteristics of the stage, including spatial resolution, accuracy and repeatability, compare imaging data generated with our device to data obtained using a commercially available microplate reader, demonstrate its suitability to high-content microscopy in 96-well high-throughput screening format and validate its applicability to automated functional Cl-- and Ca2+-imaging with recombinant HEK293 cells as a model system. A time-lapse video of the stage during operation and as part of a custom assembled screening robot can be found at https://vimeo.com/158813199.
Keywords: 3D desktop printing; Arduino; High-content screening; Cell viability; YFPI152L; Glycine receptor; TRPV1; Fluo-4 AM